Five-factor model of personality and transformational leadership. - Judge, Timothy A.; Bono, Joyce E. (Journal of Applied Psychology, 2000)
This study linked traits from the 5-factor model of personality (the Big 5) to transformational leadership behavior. Neuroticism, Extraversion, Openness to Experience, and Agreeableness were hypothesized to predict transformational leadership. Results based on 14 samples of leaders from over 200 organizations revealed that Extraversion and Agreeableness positively predicted transformational leadership; Openness to Experience was positively correlated with transformational leadership, but its effect disappeared once the influence of the other traits was controlled. Neuroticism and Conscientiousness were unrelated to transformational leadership. Results further indicated that specific facets of the Big 5 traits predicted transformational leadership less well than the general constructs. Finally, transformational leadership behavior predicted a number of outcomes reflecting leader effectiveness, controlling for the effect of transactional leadership.